2018
DOI: 10.1002/brb3.933
|View full text |Cite
|
Sign up to set email alerts
|

Low tumor necrosis factor‐α levels predict symptom reduction during electroconvulsive therapy in major depressive disorder

Abstract: ObjectiveChanges in the tumor necrosis factor‐α (TNFα) have been associated with major depressive disorder (MDD). Findings concerning the effects of electroconvulsive therapy (ECT) on the TNFα level have been contradictory. The aim was to examine the immediate and long‐term changes in the TNFα level and their associations with symptom reduction in patients with MDD during ECT.MethodThe study included 30 patients with MDD. Their TNFα levels were measured at baseline and 2 and 4 hr after the first, fifth and las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Similar to Hestad et al.,'s (2003) and Sorri et al.,'s (2018) research, our study confirmed that ECT has an effect on TNFα decrease of 10% on average. This decline in schizophrenia patients was gradual during ECT treatment and was proven to be statistically significant (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to Hestad et al.,'s (2003) and Sorri et al.,'s (2018) research, our study confirmed that ECT has an effect on TNFα decrease of 10% on average. This decline in schizophrenia patients was gradual during ECT treatment and was proven to be statistically significant (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 92%
“…In antidepressant sleep deprivation therapy, higher IL-6 levels predicted worse treatment response in depressed patients with bipolar disorder, in agreement with previous studies on antidepressants (113). Lower TNFα levels at the first ECT have also shown to predict better treatment outcome (114). However, this correlation between higher inflammatory cytokine levels and worse treatment efficacy is not found in all treatments.…”
Section: Immunomodulatory Effects Of Antidepressant and Anti-fatigue mentioning
confidence: 99%
“…Moreover, rTMS exerted antidepressant-like effects in a CUMS model via a nuclear factor-E2-related factor 2 (Nrf2)-dependent anti-inflammatory mechanism, which suppressed the production of pro-inflammatory TNF-α, iNOS, IL-1β, and IL-6 in hippocampal regions [ 112 ]. A substantial body of evidence consistently showed that ECT could alleviate pro-inflammatory cytokine secretion in depressed patients, as indicated by a notable reduction in peripheral TNFα, IL-6, eotaxin-3, and IL-5 levels [ 113 , 114 , 116 , 117 ]. Moreover, ECT was also reported to increase the level of blood IL-10 [ 115 ], which is a well-established anti-inflammatory cytokine that prevents neuronal and glial cell death [ 128 ].…”
Section: Comparison Of Fda-approved Treatments For Major Depressionmentioning
confidence: 99%